PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF TERHADAP HASIL BELAJAR DASAR-DASAR DPIB SISWA KELAS X SMK NEGERI 14 MEDAN - sinaga, Nensi; Sutrisno (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research aims to determine the effect of using interactive learning media based on the Edpuzzle platform on the learning outcomes in the Basics of Building Modeling and Information Design (DPIB) subject among tenth-grade students at SMK Negeri 14 Medan. This study employs a quasi-experimental method with a non-equivalent control group design. The research subjects consist of tenth-grade DPIB students divided into several classes. The sampling technique used is cluster random sampling, where classes were selected randomly to be designated as the experimental group and the control group. The experimental group was treated with interactive learning media based on the Edpuzzle platform, while the control group used non-interactive video-based media. Both groups were given a pretest and a posttest to identify differences in learning outcomes before and after the treatment. Data collection was conducted through learning outcome tests in the form of multiple-choice questions. The obtained data were then analyzed using statistical tests to determine the difference in learning outcomes between the experimental and control groups. The results show a significant improvement in learning outcomes in the experimental group compared to the control group. Thus, it can be concluded that the use of interactive learning media based on the Edpuzzle platform has a significant influence on the learning outcomes of the Basics of DPIB among tenth-grade students at SMK Negeri 14 Medan